START-UP CONTROL USING DC POWER SUPPLY FOR ISOLATED MODE OPERATION OF 100 kW WIND POWER PLANT - Rijanto, Estiko (P3TKEBTKE, 2010)
This paper reports design of a start-up controller for a 100 kW wind electrical power plant. The plant is designed to be able to work either in isolated or grid-connected circumstances. This paper aims at designing a controller for start-up and operation of the plant in isolated mode. Thecontroller has been designed to provide excitation voltage during the start-up and to maximize energy conversion during operation as well as to maintain the DC link voltage be at a desired value. Controller design uses vector control and hysteresis PWM approaches. From computer simulationresults it is concluded that the plant can start-up at cut in wind speed of 2.5 m/sec by maintaining DC link voltage at 96 V, and it changes over from motoring mode to generating mode in 15.5 seconds giving start-up electrical power of 761 Watt. Moreover, the controller can make the generator produce electrical power of 23.48 kW and 111.58 kW for average wind speed of 7 m/s and rated wind speed of 12 m/s, respectively.